Does Financial Statement Comparability Facilitate SEC Oversight?* - Nam, Jonathan Sangwook; Thompson, Rachel A. (Contemporary Accounting Research, 2023)
ABSTRACT This study examines the impact of cross‐firm financial statement comparability on regulatory oversight of accounting quality. Required to review each firm's periodic filings at least once every three years, the SEC learns about the degree to which a firm's accounting system is comparable to those of its peers. We posit that the SEC's ex ante knowledge about financial statement comparability, gleaned from prior‐year filing reviews, facilitates its evaluation of firms' accounting quality during the current‐year filing review. Consistent with the notion that comparable accounting systems enhance regulators' ability to identify discretionary accounting deviations, we find that the likelihood of the SEC issuing a comment letter for higher abnormal accruals increases with financial statement comparability. Further analysis reveals that the regulatory benefits from higher financial statement comparability are more salient when the SEC faces higher monitoring constraints in filing reviews. Moreover, our finding shows that comparable accounting numbers across firms help the SEC detect severe accounting violations that necessitate restatements. Overall, we provide novel evidence suggesting that higher financial statement comparability improves the efficacy of the SEC's oversight of accounting quality by reducing the information costs associated with cross‐firm comparisons.